Pengaruh Cross-Training dan Motivasi Kerja Terhadap Kinerja Karyawan di Hotel Adiwana Unagi Suites Ubud Gianyar Bali - Luh Putu Ayu Novita Dewi; Komang Shintiya Nita Kristiana Putri (Jurnal Mosaik Hospitaliti, 2026)
Hotel management must provide training and work motivation to maintain employee loyalty and quality in order to achieve good performance. One training program that can be applied is cross-training. However, the implementation of cross-training does not always run smoothly. Problems that arise include decreased employee motivation in carrying out daily tasks due to the additional workload from the cross-training program. This study analyses the effect of cross-training and work motivation on employee performance at Adiwana Unagi Suites, Ubud, Gianyar, Bali, and aims to identify the independent variable with the most dominant influence. Data were collected through observation, documentation, interviews, and questionnaires involving all 49 employees. The results show that cross-training and work motivation simultaneously have a significant effect on employee performance. This indicates that the more frequently employees receive cross-training and the higher their work motivation, the more their performance tends to improve. These two variables contribute 6.3% to employee performance, with cross-training having the stronger influence. The study recommends that hotel management continue providing cross-task training and create a pleasant work atmosphere to maintain employee enthusiasm and optimize performance